The Influence of Liquidty, Profitbality and Ratios on Company Financial Performance (Case Study of PT Garuda Indonesia’s Financial Reports on the IDX in 2020-2022) - Quraini, Nur Indah; Fauzy, Resty (Asosiasi Dosen Akuntansi Indonesia, 2023)
This research aims to determine the financial performance of PT Garuda Indonesia Tbk in terms of Liquidity, Profitability and Activity Ratios. The data form of financial reports of airline companies listed on the IDX for 2020-2022. The data collection techniques used are documentation techniques and library techniques. The results of this research prove that PT Garuda Indonesia Tbk experiences fluctuations in financial performance from year to year, which is reflected in changes in the values of liquidity ratios, profitability ratios and activity ratios. Even though there has been an increase in several ratios, the company is still faced with liquidity risk because the liquidity ratio figure is below 1. Apart from that, another challenge faced by the company is achieving better efficiency in generating net profits for shareholders and increasing the use of assets and working capital efficiently. Therefore, companies need to improve the management of their current assets, inventories, current liabilities and cash to maintain and improve better financial performance, as well as improve asset and working capital management strategies to achieve more profitable results for shareholders